Estimation dacryocystorhinostomy with temporary intubation of lacrimal canaliculi in the authors patients - Korporowicz, Danuta; Nowak, Antonina (Klinika Oczna / Acta Ophthalmologica Polonica, 2002)
The purpose of the study was to present the results of treatment of lacrimal ducts obstruction. The authors describe the advantages of temporary intubation of lacrimal canaliculi with simultaneous dacryocystorhinostomy. The findings have been based on 38 operations within a sixteen-year period. Obstruction of the lacrimal drainage pathway was due to: trauma, postinflammatory stenosis of the nasolacrimal duct, tumors and jatrogenic injuries of the nasolacrimal drainage system often following operations of the maxillary sinus. Treatment was based on clinical examination by: slit lamp exam, probing and irrigation of the lacrimal system, X-ray picture of the maxillary sinus, laryngology examination and bacteriological culture from conjunctival sac. Conclusion: Anatomical and functional results indicate the necessity of this surgery method in selected cases.